Uji Karakteristik Enzim Lipase Dari Biji Nyamplung (Calophyllum Inophyllum L) Sebagai Media Pembelajaran Biokimia dalam Bentuk Buletin - Hakim, Aliefman; Burhanuddin, Burhanuddin; Juniarly, Lalu Anugrah Dimas (Chemistry Education Practice, 2025)
This study aimed to develop a biochemistry learning media derived from experimental research on the characterization of lipase enzymes extracted from Calophyllum inophyllum (nyamplung) seeds. The development process employed a Research and Development (R&D) approach, adopting the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The study was limited to the development phase. The learning media was evaluated through two primary dimensions: validity and practicality. Data collection involved the distribution of expert validation instruments to subject-matter lecturers and practicality response instruments to students via Google Forms. A purposive sampling technique was employed, targeting Chemistry Education students from the 2020 and 2021 cohorts who had enrolled in the Biochemistry I course. A total of 30 students were randomly selected from this pool. The validity assessment conducted by expert validators yielded a score of 90.5%, indicating that the media falls within the "highly valid" category. Similarly, the practicality test, based on student responses, resulted in a score of 91.5%, which is classified as "highly practical”. These findings indicate that the developed biochemistry bulletin is both valid and practical, thus offering strong potential for use as an effective instructional tool in biochemistry learning contexts.